Hybrid evolutionary barnacles mating optimization: a novel technique for economic load dispatch optimization / Nor Laili Ismail ... [et al.] - Ismail, Nor Laili; Musirin, Ismail; Dahlan, Nofri Yenita; Mansor, Mohd Helmi (2022)
The static economic dispatch (SED) problem is concerned with lowering the fuel cost of power generators for a set period, typically an hour. Economic load dispatch aims to distribute the system's power demand evenly across all generating units. Operating expenses will be kept to a bare minimum while revenue will be maximized. This paper presents a new efficient optimization technique, Hybrid Evolutionary Programming-Barnacles Mating Optimization (HEBMO), to solve non-convex ED problems considering the valve point effect (VPE). The formulated objective function minimizes the total generation cost while satisfying the equality and inequality of the decision variables. The proposed technique is validated on IEEE 57-Bus RTS and consists of 7 generating units. Several case studies have been selected to evaluate the efficiency of HEBMO and compare it with the existing single optimization technique, Evolutionary Programming (EP), and Barnacles Mating Optimizer (BMO). The study's outcome revealed that the proposed HEBMO outperforms EP and BMO. The HEBMO results demonstrate its capability to determine the optimal load dispatched with the lowest generation cost.